FUNCTION OF AND VALUES CONTAINING IN THE STORY OF WAYANG BEBER PACITAN - Margana Margana (Proceeding of International Conference on Art, Language, and Culture, 2017)
This research aimed to find out the function of and the values containing in Wayang Beber Pacitan performance. This study was a descriptive qualitative research. Techniques of collecting data used were observation, interview, and document analysis. The sampling technique used was purposive sampling one. Data analysis was carried out using an interactive model of analysis, while data validation was conducted using triangulation. From the result of research, it can be concluded that wayang beber is a traditional art of Archipelago having distinctive peculiarity compared with other wayang types. The pecualiarity of wayang beber lies on its painting form and performing method spread (extended) out, and retold by the narrator corresponding to the content of story. The existence of wayang beber has a very important function and values for its proponents including; wayang bebers has ritual, social, and economic functions, and the story contains character education values including: responsibility, loyalty, subservience, nationalism, and persistence in reaching ideals.